2022
DOI: 10.1002/cbin.11802
|View full text |Cite
|
Sign up to set email alerts
|

TOX3 regulates the proliferation and apoptosis of colorectal cancer by downregulating RhoB via the activation of the MAPK pathway

Abstract: TOX high mobility group box family member 3 (TOX3) can function as tumor suppressor or oncogene in different tumors, while ras homolog family member B (RhoB) is a well-known tumor suppressor. The expression and role of TOX3 in colorectal cancer (CRC) are unknown. This study aimed to investigate the expression of TOX3 in CRC and the role of TOX3/mitogen-activated protein kinase (MAPK)/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…High TOX3 expression was associated with high T stage, nodal invasion, and advanced tumor stage. 41 Importantly, the Sankey plot revealed a higher risk of death in the high-risk group and a correlation between molecular subtypes with poorer prognosis and a higher risk score, supporting the prognostic relevance of the Tregs-related signature. These findings are consistent with previous studies that have shown the prognostic value of molecular subtyping in OC.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…High TOX3 expression was associated with high T stage, nodal invasion, and advanced tumor stage. 41 Importantly, the Sankey plot revealed a higher risk of death in the high-risk group and a correlation between molecular subtypes with poorer prognosis and a higher risk score, supporting the prognostic relevance of the Tregs-related signature. These findings are consistent with previous studies that have shown the prognostic value of molecular subtyping in OC.…”
Section: Discussionmentioning
confidence: 76%
“…40 Yang et al investigated the expression and role of TOX high mobility group box family member 3 in CRC. 41 Notably, the authors found that messenger RNA and protein expression levels of TOX3 were markedly upregulated in CRC tissues and cell lines. High TOX3 expression was associated with high T stage, nodal invasion, and advanced tumor stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports further confirmed that the activation of PI3K/AKT signaling might account for the anti-CRC effect of cincumol. In addition, except for PI3K/AKT signaling, there are some other important signaling pathways that was closely correlated with the progression of CRC, such as NF-κB-Nrf2 signaling 26 , Notch signaling 27 , MAPK signaling 28 , and JAK/STAT signaling 29 . We next plan to explore whether the anti-CRC activity of cincumol was related to the aberrant expression of these known signaling.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, TOX3 can mediate the expression of the apoptosis-related molecule RhoB and enhance the proliferation of colorectal tumors. 12 Moreover, TOX3 can also strengthen the metastatic ability of lung cancer cells through regulating EMT and Hippo-related signaling pathways. 13 The tripartite motif containing 56 (TRIM56, an E3 ligase) is related to the degree of malignancy of liver, lung, hematological, and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%